Alice Parfitt - Thesis submitted in partial fulfilment of the degree of Doctor of Clinical Psychology (DClinPsych) - Parfitt, A (2022)
Project 1. Background: Doctors experience high rates of mental ill-health. Effective treatments and specialist services exist, yet there are significant barriers to disclosure and help- seeking. These barriers are concerning given the negative impact on doctors’ health and recovery, staff turnover and the quality of care provided. It is therefore important to understand these barriers and facilitators in more detail to improve access to support and services.